Analisis Budaya Keselamatan Pasien oleh Bidan dan Perawat dalam Pelayanan Rawat Inap di RS X Semarang - Wahyu Nursetiawan; Sudiro Sudiro; Chriswardani Suryawati (Jurnal Manajemen Kesehatan Indonesia, 2020)
Patient safety is a system that makes patient care in the hospital safer and prevent injuries caused by mistakes due to carrying out an action or not taking the action that should be taken. This study aimed to analyze the influence of patient safety culture, factors that influence and availability of resources on prevention of adverse events in the installation of inpatient services at RS X Semarang.This type of research was quantitative with a cross sectional approach. The sample was all members of the population consisting of midwives and nurses at RS X  as many as 31 employees. Data collected using structured questionnaire. Data analyzed by Chi Square test and Logistic Regression.The results showed that the majority of respondents had a supportive patient safety culture (80.6%), half of the respondents had influential factors (51.6%), half of the respondents had the availability of good resources (51.6%), and make efforts to prevent KTD (71%). There was sigificant relationship between patient safety culture and efforts to prevent KTD (p value = 0.004), there was no significant relationship between availability of resources and efforts to prevent KTD (p value = 0.113), and there was an influence between the patient safety culture on efforts to prevent KTD (p value = 0.012); OR = 0.031; CI = 0.002 - 0.467. The patient safety culture has been shown to have an influence on efforts to prevent KTD.